Human SIRT6 promotes DNA-end resection through CtIP deacetylation - Kaidi, Abderrahmane (2010)
SIRT6 belongs to the sirtuin family of protein lysine deacetylases (KDACs) that regulates ageing and genome stability. Here, we report a role for human SIRT6 in promoting DNA-end resection, a crucial step in DNA double-strand break (DSB) repair by homologous recombination (HR). SIRT6 depletion impairs the accumulation of replication protein A (RPA) and single-stranded DNA (ssDNA) at DNA-damage sites, reduces rates of HR and sensitises cells to DSB-inducing agents. We identify the DSB-resection protein CtIP as a SIRT6 interaction partner and show that SIRT6-dependent CtIP deacetylation promotes resection. A non-acetylatable CtIP mutant alleviates the effect of SIRT6 depletion on resection, thus identifying CtIP as a key substrate by which SIRT6 facilitates DSB processing and HR. These findings further define how SIRT6 promotes genome stability.